2023
DOI: 10.1021/acsestengg.3c00172
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic and Organic Silicon Fouling of Nanofiltration Membranes during Pilot-Scale Direct Potable Reuse

Abstract: Fouled nanofiltration membranes from lead and lag positions of a 2-stage pilot-scale direct potable reuse plant treating secondary municipal wastewater effluent in El Paso, Texas were thoroughly characterized after 9 months of operation to elucidate the role of silicon moieties on fouling. X-ray photoelectron (XPS), energy dispersive X-ray (EDS), and Fourier transform infrared (FTIR) spectroscopies identified silicon oxides/ silica as dominant foulants, especially on the lag element. Gas chromatography/mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
(173 reference statements)
0
3
0
Order By: Relevance
“…A flow-through pH meter was used to simultaneously monitor the solution pH at the exit of the EC cell during the operation. The system was run with the same synthetic wastewater secondary effluent , as described in Table S1 [Supporting Information, SI], at pH 7.0 ± 0.2, with the overall potential, conductivity, and solution pH continuously monitored. Air was continuously sparged to increase the dissolved oxygen (DO) concentration to levels above 9 mg/L at the beginning of EC.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A flow-through pH meter was used to simultaneously monitor the solution pH at the exit of the EC cell during the operation. The system was run with the same synthetic wastewater secondary effluent , as described in Table S1 [Supporting Information, SI], at pH 7.0 ± 0.2, with the overall potential, conductivity, and solution pH continuously monitored. Air was continuously sparged to increase the dissolved oxygen (DO) concentration to levels above 9 mg/L at the beginning of EC.…”
Section: Methodsmentioning
confidence: 99%
“…Silica and hardness removal is an important function of many raw and process water treatment trains. Irreversible membrane fouling, such as mineral scaling, which limits the degree of water recovery under high pressure, and the high operational cost are the primary drawbacks of membrane technologies. , Recent studies show that EC has high potential for silica and hardness removal from various waters (e.g., groundwater, cooling tower blowdown water, and oil-sand produced water), ,, so it can serve as a pretreatment step prior to membrane separation, within the overall water treatment train . Integrating EC with membrane filtration can further improve the quality of the discharged water .…”
Section: Introductionmentioning
confidence: 99%
“…Fouling of NF membranes by silica, linear, and cyclic siloxanes was observed, along with mineral scaling and organic fouling, which led to the irreversibility of fouling. This integrated fouling situation led to a rapid decline in NF productivity and showed the current need for serious novel antiscalants for fouling issues (Abada et al, 2023;Guo et al, 2020 have demonstrated in their work that fouling due to interactive organic molecules (polysaccharides, proteins, and fulvic acid) was more significant than individual organic molecules. Mixed matrix membrane embedded with 1.0 wt% aminefunctionalized boron nitride (AFBN) showed the highest Reactive Blue 19 rejection (99.7%), the lowest contact angle (51.7 °), the highest degree of fouling (FRR of 90.4%), and the highest dye solution permeability (48 L m −2 .…”
Section: Nanofiltrationmentioning
confidence: 99%